Citizens’ Most Used Media of Interaction with the Local Governments in Nigeria - Unegbu, Vincent Enyeribe (Information Management and Business Review, 2013)
Information is a powerful instrument to prevent crimes if properly disseminated. Sources and channels of information play important roles in its utilization. It is on this backdrop that this survey was carried out to ascertain the appropriate media and channels to convey local governments’ information to the citizens. Thirteen local governments in Imo State, one of the 36 states of Nigeria, were surveyed with the use of questionnaire. Out of 1840 selected respondents, 1785 returned their questionnaire. The data generated were analyzed using Statistical Package for Social Sciences and the results were presented in discrete figures, percentages, and graphs. The study revealed that over 60 percent of the respondents got information about their local government from verbal/oral sources, radio broadcasts, schools, churches or mosques, traditional rulers and ward councillors. The sources of information were mediated because they were from local government employees who dance to the tune of their employers. The paper recommended that village youth leaders and women leaders should be involved in information dissemination in the localities.